MEDIA PEMBELAJARAN ANIMASI TIGA DIMENSI DENGAN METODE DISCOVERY LEARNING DALAM MENINGKATKAN KETERAMPILAN MENULIS TEKS DESKRIPSI SISWA SMP - Khairunnissah Khairunnissah; Sintowati Rini Utami; Suhartini Suhartini (Program Studi Pendidikan Bahasa Indonesia, STKIP Bina Bangsa Getsempena, 2023)
This study aims to improve the writing skills of description text using Discovery Learning Method through Three-Dimensional Animation media for students of class VII G SMP Negeri 7 Jakarta. The subjects in this study consisted of 30 students. This research consisted of three cycles. Each cycle consists of four stages, namely planning, implementation, observation, and reflection. Data collection techniques used in this study were observation, questionnaires, interviews, tests, and documentation. The collected data were analyzed using qualitative descriptive analysis techniques supported by quantitative data. The results of this study indicate that students of class VII G have the ability based on the results of learning activities and student scores. Thus, the application of Discovery Learning method through Three-Dimensional Animation media has been designed and used to improve description text writing skills in detailing objects. The increase obtained from the pre-cycle stage to cycle 3 with an average of 66.87 pre-cycle, 71.83 cycle 1, 77.87 cycle 2 and 86.57 cycle 3. Based on the results of the study, it can be concluded that the Discovery Learning Method through Three-Dimensional Animation Media can improve the ability to write description texts in class VII G students of SMP Negeri 7 Jakarta.AbstrakPenelitian ini bertujuan untuk mengetahui peningkatan keterampilan menulis teks deskripsi dengan Metode Discovery Learning melalui Media Animasi Tiga Dimensi pada siswa kelas VII G SMP Negeri 7 Jakarta. Subjek pada penelitian ini terdiri dari 30 siswa. Hasil penelitian ini menunjukkan bahwa siswa kelas VII G memiliki kemampuan berdasarkan hasil aktivitas belajar dan nilai siswa. Dengan demikian, penerapan Metode Discovery Learning melalui media Animasi Tiga Dimensi telah dirancang dan digunakan untuk meningkatkan keterampilan menulis teks deskripsi dalam merincikan objek secara detil. Adapun peningkatan yang diperoleh mulai dari tahap prasiklus hingga siklus 3 dengan rata-rata prasiklus 66,87, siklus 1 71,83, siklus 2 77,87 dan siklus 3 86,57. Berdasarkan hasil penelitian, dapat disimpukan bahwa Metode Discovery Learning melalui Media Animasi Tiga Dimensi dapat meningkatkan kemampuan menulis teks deskripsi pada siswa kelas VII G SMP Negeri 7 Jakarta.